Sustainability Potential of Kikuyu Grass (Pennisetum clandestinum) in Livestock Farming of Peru’s Highland Regions. - Alvarez-García, W. (2024)
Sustainable Kikuyu (Pennisetum clandestinum) production in the Peruvian highlands was evaluated through productivity, growth, and chemical composition. This study assessed the effects of nitrogen (N) rate, organic matter application, and cutting frequency on Kikuyu grass’s yield, chemical composition, plant height, and growth rate. The experiment followed a randomised block design with split plots. A multivariate analysis of variance (MANOVA) assessed the differences across study factors. Applying 120 kg of N ha−1 yr−1 raised the protein yield to 3454.53 kg ha−1, with a crude protein (CP) content of 23.54%. Moreover, fencing with cypress (Cupressus lusitanica) trees influenced the Kikuyu biomass, producing 19,176.23 kg of dry matter (DM) ha−1 yr−1 at 8.5–11.5 m from the tree base. Organic matter enhanced the Kikuyu aboveground biomass. While dry matter production showed no significant difference between 30- and 60-day cutting intervals, CP content was higher at 30 days (p < 0.05). Peak daily dry matter (DM) production occurred at 45 days, achieving a biomass accumulation of 21,186.9 kg of DM ha−1 yr−1. Given its high yield and favourable chemical composition, Kikuyu is a viable option for dairy cattle feed, especially in highland areas. Implementing a plant improvement programme for Kikuyu could further enhance its nutritional value for high-production dairy cows.